2018
DOI: 10.1002/jsfa.9321
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of triadimefon and residue levels of metabolite triadimenol: tracing rapeseed from harvesting and storage to household oil processing

Abstract: Different storage conditions and food processing could reduce the pesticide level to a greater or lesser extent. However, it is not easy to eliminate or significantly weaken triadimenol once triadimefon has degraded completely. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Similarly, Li et al . also found that the concentration of triadimenol in rapeseed oil was significantly higher than that in meal after rapeseed pressing 17 . Moreover, the correlation between pesticide hydrophobicity ( K ow ) and their PF in peanut oil was analyzed.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Similarly, Li et al . also found that the concentration of triadimenol in rapeseed oil was significantly higher than that in meal after rapeseed pressing 17 . Moreover, the correlation between pesticide hydrophobicity ( K ow ) and their PF in peanut oil was analyzed.…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, Li et al also found that the concentration of triadimenol in rapeseed oil was significantly higher than that in meal after rapeseed pressing. 17 Moreover, the correlation between pesticide hydrophobicity (K ow ) and their PF in peanut oil was analyzed. The results showed that the Pearson correlation coefficient was 0.925 (P < 0.05), indicating that there was a significant positive correlation between log K ow of pesticide and PF in peanut oil (Fig.…”
Section: Processing Of Peanutmentioning
confidence: 99%
See 2 more Smart Citations
“…In thermal processing, the processing conditions, such as temperature, duration and presence or absence of fluid and certain physicochemical properties of pesticides, have an impact on the removal of pesticide residues. As the temperature increases, the pesticide volatilizes, hydrolyzes or thermally degrades, resulting in a decrease in its concentration [ 37 ]. From the results of steaming and boiling, lower concentrations of penthiopyrad were obtained compared to the initial data, regardless of whether there was liquid contact during processing, and the determined PF was <1.…”
Section: Discussionmentioning
confidence: 99%